Preparation method of soft ultrahigh-elasticity FDY (fully drawn yarn) fiber with improved air permeability

By using composite spinning of PET, polyamide, and PTT, along with optimized spinneret settings and heat treatment processes, the problems of insufficient breathability and softness in polyester-type bicomponent composite fibers were solved, enabling the preparation of high-strength, high-elasticity, and soft FDY fibers.

CN119287537AActive Publication Date: 2025-01-10WUXI XINGSHENG NEW MATERIAL TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411224304.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-10
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

Existing polyester-based bicomponent composite fibers lack sufficient breathability and softness in their manufacturing process, making it difficult to meet the requirements for skin-friendly fabrics.

Method used

Composite spinning was carried out using three polymers: PET, polyamide, and PTT. The process parameters of FDY were optimized by combining gourd-shaped and hollow spinnerets with ring blowing cooling and relaxation heat treatment, and adding composite agents such as n-octyl phthalate, silicone oil, and carbon nanotubes.

Benefits of technology

It improves the strength, elongation and elasticity of the fiber, enhances the breathability and softness of the fiber, strengthens the fluffiness and coverage of the fabric, and improves the mechanical properties and hand feel of the fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287537A_ABST
    Figure CN119287537A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of soft ultrahigh-elasticity FDY (fully drawn yarn) fibers with improved air permeability, which comprises the following steps: S1, respectively slicing PET (polyethylene terephthalate), polyamide and PTT (polytrimethylene terephthalate), then melting the PET, the polyamide and a complexing agent in a mass ratio of 1: 1: (0.05-0.1), extruding through a first spinneret plate, directly melting the PTT, and extruding through a second spinneret plate; the complexing agent is prepared from n-octyl phthalate, silicone oil and a carbon nanotube; the first spinneret plate is provided with gourd-shaped spinneret orifices, and the second spinneret plate is provided with hollow spinneret orifices; and S2, carrying out FDY process and relaxation heat treatment in sequence to obtain the FDY fiber. According to the invention, three polymers of PET, polyamide and PTT are subjected to composite spinning, and the difference of thermal shrinkage performance of two components is utilized in parallel composite spinning, so that the fiber can generate durable, stable and elastic curl, and the improvement of the fiber performance can be facilitated: the loose degree, strength, elasticity and other performance of the fiber can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of FDY fibers, and in particular to a method for preparing soft ultra-elastic FDY fibers with improved air permeability. Background Art

[0002] FDY fiber, full name of fully drawn yarn, is a synthetic fiber that introduces stretching during the spinning process. This fiber is characterized by high orientation and medium crystallinity, which makes FDY fiber feel smooth and soft, and is often used to weave simulated silk fabrics. FDY fiber is widely used in the textile field due to its excellent performance. However, with the development of technology, researchers are still exploring new methods to further improve the performance of FDY fiber or reduce costs. The FDY production process is a complex and critical spinning process. By controlling key parameters such as temperature and stretching multiples, strengthening quality inspection, and producing high-quality FDY yarn, it can meet more needs, while paying attention to environmental protection and achieving sustainable development.

[0003] The properties of fibers made from different polymer raw materials are completely different, each with its own advantages and disadvantages. It is for this reason that different fiber properties are combined to make products to give full play to their respective advantages. Among them, the parallel two-component composite fiber uses the difference in the thermal shrinkage properties of the two components to make the fiber bend away from the fiber axis, showing a permanent spiral curl. This curl has the characteristics of long-lasting stability and good elasticity, which can give the fabric better elasticity, fluffiness and coverage, and is widely used in clothing. However, the preparation process of polyester two-component composite fibers is demanding, mainly because the flow state of the polymer melt in the spinneret hole must be controlled. However, because polyester two-component composite fibers are widely used in a variety of skin-friendly fabrics, their breathability and softness need to be further improved. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing soft ultra-elastic FDY fiber with improved air permeability.

[0005] The technical solution of the present invention is: a method for preparing soft ultra-high elastic FDY fiber with improved air permeability, comprising the following steps:

[0006] S1, slicing PET, polyamide and PTT respectively, then melting PET, polyamide and compounding agent in a mass ratio of 1:1:0.05-0.1, and extruding through a first spinneret, and then directly melting PTT and extruding through a second spinneret, the mass ratio of PET:PTT is 3:1-2;

[0007] The composite agent is made of n-octyl phthalate, silicone oil and carbon nanotubes; the first spinneret adopts a gourd-shaped spinneret hole, and the second spinneret adopts a hollow spinneret hole;

[0008] The number of the gourd-shaped spinnerets is a, the number of the hollow spinnerets is b, a:b is 3-4:8-9; the diameters of the gourd-shaped spinnerets are d1 and d2 respectively, the diameter of the hollow spinneret is d3, and d1=1.6-1.7d2, d3=d2;

[0009] S2. After extrusion through the first spinneret and the second spinneret, fiber filaments are obtained, and the fiber filaments are spun in parallel to form a fiber filament, and then cooled by ring blowing, the temperature of the ring blowing is 20-30°C, and the wind speed is 0.5-1.4m / s, and then the FDY process and relaxation heat treatment are carried out in sequence to obtain FDY fiber.

[0010] Description: Through the above method, PET, polyamide and PTT three types of polymers are composite spun, and the different properties of the above fibers can be combined to make products, giving full play to their respective advantages. The parallel composite spinning utilizes the difference in thermal shrinkage properties of the two components to make the fibers produce lasting, stable and elastic curls, giving the fabric better elasticity, fluffiness and coverage. The different settings of the gourd-shaped spinneret holes and the hollow spinneret holes can help improve the fiber properties: improve the mechanical properties of the fibers such as strength, elongation, and elasticity; the relative setting of the number of spinneret holes can make the matching of the gourd-shaped spinneret holes and the hollow spinneret holes better; the wind speed setting can make the fiber structure uniform and avoid fusion; and if the wind speed exceeds the range, it may lead to uneven fiber structure or rough or broken surface.

[0011] Furthermore, the aspect ratio of the gourd-shaped spinneret hole is 2 to 3, and the diameter in the aspect ratio is d1.

[0012] Note: The above-mentioned further setting of the aspect ratio of the gourd-shaped spinneret can improve the fiber performance and further optimize the fiber structure.

[0013] Furthermore, d2 is 0.15 to 0.3 mm.

[0014] Furthermore, in the FDY process, the FDY pre-network pressure is 0.05-0.2 MPa, the speed parameters are: the first roller speed is 2200-2280 m / min, the second roller speed is 3000-3200 m / min, and the winding speed is 2900-3000 m / min.

[0015] Furthermore, in the FDY process, the temperature parameters are: the spinning temperature is 272-275°C, the temperature of the first roller is 82-89°C, and the temperature of the second roller is 140-145°C.

[0016] Note: By limiting the FDY process parameters as above, the quality of the FDY fiber products can be guaranteed: by controlling parameters such as temperature, operating speed, spinneret diameter, stretch ratio and network pressure, the FDY fiber has stable performance indicators, such as strength, elongation at break and other properties, thereby improving production efficiency.

[0017] Further, the method of the relaxation heat treatment is:

[0018] First, the composite gas is filled into the relaxation heat treatment equipment, and infrared heating is used to raise the temperature to 90-95°C, and the treatment is allowed to stand for 5-8 minutes. Then, the temperature is raised to 100-105°C, and the treatment is allowed to stand for 3-4 minutes. Then, the temperature is raised to 110-115°C, and the treatment is allowed to stand for 3-4 minutes. Then, the treatment is completed.

[0019] The composite gas is N2 and CO2 in a mass ratio of 1:1.

[0020] Description: The above-mentioned relaxation heat treatment method can make the fiber structure looser, thereby improving the feel of the fiber, making it softer and more comfortable, and significantly improving the feel of the fabric obtained from the fiber; at the same time, the fluffiness is increased: the relaxation heat treatment can cause the fiber to produce a certain degree of uneven shrinkage under the action of wet heat, so that the fiber will have improved thermal stability and less prone to deformation after being further processed into fabric; at the same time, it helps to improve the elasticity and other properties of the fiber.

[0021] Furthermore, the first static treatment is: filling 30% volume fraction of water vapor into the relaxation heat treatment equipment, and adjusting the pressure to 0.16-0.18MPa; the second static treatment is: filling 10% volume fraction of water vapor into the relaxation heat treatment equipment, and adjusting the pressure to 0.20-0.22MPa; the third static treatment is: adjusting the pressure to 0.16-0.18MPa.

[0022] Note: The above further treatment can strengthen the treatment effect of the relaxation heat treatment. By pressurizing and adding moisture, the above uneven shrinkage effect and thermal stability can be enhanced, thereby enhancing the elastic properties of the fiber.

[0023] Furthermore, the preparation method of the composite agent is:

[0024] S1-1, first pre-treating the carbon nanotubes, the pre-treating method being: mixing the carbon nanotubes with 70% by mass concentrated nitric acid at a ratio of 1g:1ml, and soaking at 60-70°C for 2-3h; then rinsing the carbon nanotubes with deionized water, and drying at 60°C for 4-5h; obtaining the pre-treated carbon nanotubes;

[0025] S1-2. Prepare n-octyl phthalate, silicone oil and pretreated carbon nanotubes in a mass ratio of 3:1 to 2:1, and then use a microfluidizer to mix them for 10 to 20 minutes to obtain a composite agent. The frequency of the microfluidizer is 100 to 150 times / s, and the working pressure of the microfluidizer is 300 to 350 MPa.

[0026] Description: The addition of the above-mentioned compounding agent can improve the performance of FDY fiber in many aspects and increase the use value of the fiber. Octyl phthalate can improve the plasticity of FDY fiber, making it easier to handle during processing. At the same time, it can also improve the feel of the fiber, making it softer and more comfortable, and improve the dyeing performance. Silicone oil effectively reduces the friction and wear of the fiber during processing, improves the gloss of the fiber, improves the antistatic performance of the fiber, and makes the fiber more stable during processing and use; carbon nanotubes improve the mechanical properties and thermal stability of the fiber.

[0027] Furthermore, in step S1-1, after soaking for 2 to 3 hours, the carbon nanotubes are subjected to a plasma treatment in a plasma atmosphere, wherein the power of the first plasma treatment is 400 to 500 W and the time is 3 to 10 seconds. After being rinsed with deionized water, the carbon nanotubes are subjected to a secondary plasma treatment in a plasma atmosphere, wherein the power of the secondary plasma treatment is 600 to 650 W and the time is 2 to 3 seconds, and the plasma is argon.

[0028] Description: Through the above method, the surface properties of carbon nanotubes can be enhanced, thereby enhancing the dispersibility, and then evenly dispersing them in the system to improve the performance of FDY fibers.

[0029] The beneficial effects of the present invention are:

[0030] (1) The present invention can utilize the different properties of the above fibers to make products by composite spinning of three types of polymers, namely PET, polyamide and PTT, and give full play to their respective advantages. The parallel composite spinning utilizes the difference in thermal shrinkage properties of the two components to make the fibers produce a long-lasting, stable and elastic curl, giving the fabric better elasticity, fluffiness and covering properties. The different settings of the gourd-shaped spinneret holes and the hollow spinneret holes can help improve the fiber properties: improve the mechanical properties of the fibers, such as strength, elongation, and elasticity; the relative setting of the number of spinneret holes can make the matching of the gourd-shaped spinneret holes and the hollow spinneret holes to be better; the wind speed setting can make the fiber structure uniform and avoid fusion; if the wind speed exceeds the range, it may cause the fiber structure to be uneven or the surface to be rough or broken.

[0031] (2) The setting of the relaxation heat treatment of the present invention can make the structure of the fiber looser, thereby improving the feel of the fiber, making it softer and more comfortable, and significantly improving the feel of the fabric obtained from the fiber; at the same time, the fluffiness is increased: the relaxation heat treatment can make the fiber produce a certain degree of uneven shrinkage under the action of wet heat, so that the fiber can improve thermal stability and is not easy to deform after being further processed into fabric; at the same time, it helps to improve the elasticity and other properties of the fiber. By adding a composite agent, the performance of FDY fiber can be improved from multiple aspects, and the use value of the fiber can be improved. Octyl phthalate can improve the plasticity of FDY fiber, making it easier to handle during processing. At the same time, it can also improve the feel of the fiber, making it softer and more comfortable, and improve the dyeing performance. Silicone oil effectively reduces the friction and wear of the fiber during processing, improves the gloss of the fiber, improves the antistatic performance of the fiber, and makes the fiber more stable during processing and use; carbon nanotubes improve the mechanical properties and thermal stability of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a data chart showing the influence of FDY process parameters on the elongation at break and curl stability performance of FDY fiber in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.

[0034] Embodiment 1:

[0035] A method for preparing soft ultra-elastic FDY fiber with improved air permeability comprises the following steps:

[0036] S1, slicing PET, polyamide and PTT respectively, then melting PET, polyamide and compounding agent at a mass ratio of 1:1:0.08 and extruding through a first spinneret, then directly melting PTT and extruding through a second spinneret, the mass ratio of PET:PTT being 3:1.5;

[0037] The composite agent is made of n-octyl phthalate, silicone oil and carbon nanotubes; the first spinneret adopts a gourd-shaped spinneret hole, and the second spinneret adopts a hollow spinneret hole;

[0038] The number of the gourd-shaped spinneret holes is a, the number of the hollow spinneret holes is b, a:b is 3:9; the diameters of the gourd-shaped spinneret holes are d1 and d2 respectively, the diameter of the hollow spinneret hole is d3, and d1=1.6d2, d3=d2; d2 is 0.2 mm. The aspect ratio of the gourd-shaped spinneret hole is 2, and the diameter in the aspect ratio is d1.

[0039] S2. After extrusion through the first spinneret and the second spinneret, fiber filaments are obtained, and the fiber filaments are formed into a fiber filament by a parallel composite spinning method, and then cooled by ring blowing. The temperature of the ring blowing is 205°C and the wind speed is 0.9m / s. Then, the FDY process and relaxation heat treatment are carried out in sequence to obtain FDY fibers.

[0040] In the FDY process, the FDY pre-network pressure is 0.1 MPa, the speed parameters are: the first roller speed is 2250 m / min, the second roller speed is 3100 m / min, and the winding speed is 2950 m / min;

[0041] The temperature parameters are: spinning temperature is 273°C, first roller temperature is 85°C, and second roller temperature is 142°C.

[0042] The relaxation heat treatment method is: first, fill the relaxation heat treatment equipment with a composite gas, use infrared heating to raise the temperature to 93°C, let it stand for 6 minutes, then raise the temperature to 103°C, let it stand for 3 minutes, then raise the temperature to 113°C, let it stand for 3 minutes, and then complete the treatment; the composite gas is N2 and CO2 in a mass ratio of 1:1.

[0043] Example 2: This example is different from Example 1 in that the raw material components are different. PET, polyamide, and PTT are sliced ​​separately, and then PET, polyamide, and compounding agent are melted at a mass ratio of 1:1:0.05, and the mass ratio of PET:PTT is 3:1.

[0044] Example 3: This example is different from Example 1 in that the raw material components are different. PET, polyamide, and PTT are sliced ​​separately, and then PET, polyamide, and compounding agent are melted at a mass ratio of 1:1:0.1, and the mass ratio of PET:PTT is 3:2.

[0045] Embodiment 4: This embodiment is different from Embodiment 1 in that the number of spinneret holes of the first spinneret and the number of spinneret holes of the second spinneret are different, and the ratio of a:b is 4:8.

[0046] Embodiment 5: This embodiment is different from Embodiment 1 in that the number of spinneret holes of the first spinneret and the number of spinneret holes of the second spinneret are different, and the ratio of a:b is 4:9.

[0047] Example 6: This example is different from Example 1 in that the spinneret holes have different sizes, the diameters of the gourd-shaped spinneret holes are d1 and d2 respectively, the diameter of the hollow spinneret hole is d3, and d1=1.7d2, d2 is 0.3 mm. The aspect ratio of the gourd-shaped spinneret hole is 3.

[0048] Example 7: This example is different from Example 1 in that the spinneret holes have different sizes, the diameters of the gourd-shaped spinneret holes are d1 and d2 respectively, the diameter of the hollow spinneret hole is d3, and d1=1.7d2, d2 is 0.15 mm. The aspect ratio of the gourd-shaped spinneret hole is 2.

[0049] Example 8: This example is different from Example 1 in that the FDY process parameters are different. The FDY pre-network pressure is 0.05 MPa, and the speed parameters are: the speed of one roller is 2280 m / min, the speed of the second roller is 3200 m / min, and the winding speed is 2900 m / min; the temperature of the annular air is 20°C and the wind speed is 0.5 m / s.

[0050] Example 9: This example is different from Example 1 in that the FDY process parameters are different. The FDY pre-network pressure is 0.2 MPa, and the speed parameters are: one roller speed is 2200 m / min, the second roller speed is 3000 m / min, and the winding speed is 3000 m / min; the temperature of the annular air is 30°C, and the wind speed is 1.4 m / s.

[0051] Example 10: This example is different from Example 1 in that the FDY temperature parameters are different, the spinning temperature is 272°C, the temperature of the first roller is 82°C, and the temperature of the second roller is 140°C.

[0052] Example 11: This example is different from Example 1 in that the FDY temperature parameters are different, the spinning temperature is 275°C, the temperature of the first roller is 89°C, and the temperature of the second roller is 145°C.

[0053] Example 12: This example is different from Example 1 in that the relaxation heat treatment parameters are different. The temperature is raised to 95°C, allowed to stand for 8 minutes, then raised to 105°C, allowed to stand for 3 minutes, then raised to 110°C, allowed to stand for 4 minutes three times, and then the treatment is completed.

[0054] Example 13: This example is different from Example 1 in that the relaxation heat treatment parameters are different. The temperature is raised to 90°C, allowed to stand for 5 minutes, then the temperature is raised to 100°C, allowed to stand for 4 minutes, then the temperature is raised to 115°C, allowed to stand for 3 minutes three times, and then the treatment is completed.

[0055] Example 14: The difference between this example and Example 1 is that the first static treatment is: filling the relaxation heat treatment equipment with 30% volume fraction of water vapor, and adjusting the pressure to 0.167MPa; the second static treatment is: filling the relaxation heat treatment equipment with 10% volume fraction of water vapor, and adjusting the pressure to 0.21MPa; the third static treatment is: adjusting the pressure to 0.17MPa.

[0056] Example 15: The difference between this example and Example 14 is that the static treatment parameters are different. The pressure is adjusted to 0.16 MPa for the first static treatment; the pressure is adjusted to 0.22 MPa for the second static treatment; and the pressure is adjusted to 0.18 MPa for the third static treatment.

[0057] Example 16: The difference between this example and Example 14 is that the static treatment parameters are different. The pressure is adjusted to 0.18 MPa for the first static treatment; 0.20 MPa for the second static treatment; and 0.16 MPa for the third static treatment.

[0058] Example 17: This example is different from Example 14 in that the preparation method of the composite agent is:

[0059] S1-1, first pre-treating the carbon nanotubes, the pre-treating method being: mixing the carbon nanotubes with 70% by mass concentrated nitric acid at a ratio of 1 g:1 ml, and soaking at 65° C. for 2.5 h; then rinsing the carbon nanotubes with deionized water, and drying at 60° C. for 4.5 h; obtaining the pre-treated carbon nanotubes;

[0060] S1-2. Prepare n-octyl phthalate, silicone oil and pretreated carbon nanotubes in a mass ratio of 3:1.5:1, and then use a microfluidizer to mix them for 15 minutes to obtain a composite agent. The frequency of the microfluidizer is 125 times / s, the working pressure of the microfluidizer is 325 MPa, and the microjet uses the NanoGenizer microjet high-pressure homogenizer in the prior art.

[0061] Example 18: The difference between this example and Example 17 is that, S1-1, soaking at 60°C for 3 hours; then rinsing the carbon nanotubes with deionized water, and then drying at 60°C for 5 hours to obtain pretreated carbon nanotubes; S1-2, preparing n-octyl phthalate, silicone oil and pretreated carbon nanotubes in a mass ratio of 3:2:1, and then using a microfluidizer to mix for 20 minutes to obtain a composite agent, the frequency of the microfluidizer is 150 times / s, and the working pressure of the microfluidizer is 350MPa.

[0062] Example 19: The difference between this example and Example 17 is that, S1-1, soaking at 70°C for 2h; then rinsing the carbon nanotubes with deionized water, and then drying at 60°C for 4h to obtain pretreated carbon nanotubes; S1-2, preparing n-octyl phthalate, silicone oil and pretreated carbon nanotubes in a mass ratio of 3:1:1, and then using a microfluidizer to mix for 10min to obtain a composite agent, the frequency of the microfluidizer is 100 times / s, and the working pressure of the microfluidizer is 300MPa.

[0063] Example 20: The difference between this example and Example 17 is that after soaking for 2.5 hours, the carbon nanotubes are subjected to a plasma treatment in a plasma atmosphere, the power of which is 450 W and the time is 8 seconds. After being rinsed with deionized water, the carbon nanotubes are subjected to a secondary plasma treatment in a plasma atmosphere, the power of which is 625 W and the time is 2 seconds, and the plasma is argon.

[0064] Example 21: The difference between this example and Example 20 is that the primary plasma treatment power is 400 W and the time is 10 s. After rinsing with deionized water, the carbon nanotubes are subjected to secondary plasma in a plasma atmosphere. The secondary plasma treatment power is 650 W and the time is 3 s.

[0065] Example 22: The difference between this example and Example 20 is that the primary plasma treatment power is 500 W and the time is 3 s. After rinsing with deionized water, the carbon nanotubes are subjected to secondary plasma in a plasma atmosphere. The secondary plasma treatment power is 600 W and the time is 2 s.

[0066] Experimental Example: The FDY fibers obtained in Examples 1 to 22 were subjected to performance tests, and the test results are as follows:

[0067] The water absorption of the FDY fiber obtained in Example 1 can reach 1.5%;

[0068] like Figure 1 As shown, the curl stability and elongation at break of the FDY fibers obtained in Examples 1 to 22 are shown in the data in the figure,

[0069] The performance parameters of the FDY fibers obtained in Examples 1 to 22 are as follows: elongation at break of 50-60%; breaking strength of 5-8.0 cN / dtex; single filament fineness of 0.5-1.5 dtex; crimp stability of 80-85%;

[0070] Fibers with a higher elongation at break feel softer and can buffer the force during textile processing, reducing the occurrence of lint and broken ends; fibers with a higher breaking strength have a stronger load-bearing capacity and can withstand greater external forces without breaking; fibers with a smaller single-filament fineness usually feel softer and more comfortable; fibers with a higher curl stability usually have better elasticity and a softer feel; improving curl stability and elongation at break can significantly improve the air permeability of fiber fabrics;

[0071] Comparative Example 1: The difference from Example 1 is that PET is used as the raw material;

[0072] Comparative Example 2: The difference from Example 1 is that both the first spinneret and the second spinneret use conventional circular spinneret holes;

[0073] Comparative Example 3: The difference from Example 1 is that the relaxation heat treatment method is: placing at a constant temperature of 95°C for 20 minutes;

[0074] Comparative Example 4: The difference from Example 1 is that no compounding agent is added;

[0075] 1. Explore the effects of different preparation methods on the properties of the obtained FDY fibers;

[0076] Example 1 and Comparative Examples 1 to 4 were compared, as shown in Table 1;

[0077] Table 1 Effects of different preparation methods on the properties of the obtained FDY fibers

[0078]

[0079] As shown in Table 1,

[0080] By comparing Example 1 with Comparative Example 1, it can be seen that in Example 1, the composite spinning of three types of polymers, PET, polyamide and PTT, as raw materials, can make the fiber produce a long-lasting, stable and elastic curling effect, thereby improving various properties;

[0081] By comparing Example 1 with Comparative Example 2, it can be found that the conventional spinneret holes used in Example 1 are helpful to improve the fiber properties, and the mechanical properties of the obtained fibers, such as strength, elongation, elasticity, etc., are all good;

[0082] By comparing Example 1 with Comparative Example 3, it can be found that the relaxation heat treatment method in Example 1 is more preferred. The relaxation heat treatment in Example 1 by filling with composite gas and setting the temperature gradient can further improve the fiber performance and enhance the stability.

[0083] By comparing Example 1 with Comparative Example 4, it can be found that the addition of the compounding agent in Example 1 can significantly increase the elongation at break and the curling stability, thereby improving the feel of the fiber.

[0084] 2. Explore the effects of different FDY process parameter settings on the properties of the obtained FDY fibers;

[0085] like Figure 1 As shown, among Examples 1 to 13, the parameters of Example 1 are more preferred; the parameters such as temperature, running speed, spinneret diameter, stretch ratio and network pressure can make the FDY fiber have stable performance indicators, such as strength, elongation at break and other properties. The parameters of Example 1 are more suitable, and the performance results of the other examples are slightly reduced;

[0086] 3. Explore the effects of different heat relaxation treatment parameters on the properties of the obtained FDY fibers;

[0087] Comparative Example 5: The difference from Example 1 is that in the relaxation heat treatment, the pressure is not adjusted in the first, second and third static treatments; specifically, the first static treatment is: filling the relaxation heat treatment equipment with 30% volume fraction of water vapor; the second static treatment is: filling the relaxation heat treatment equipment with 10% volume fraction of water vapor; the third static treatment is a placement treatment;

[0088] Examples 14 to 16 and Comparative Example 5 were compared, as shown in Table 2;

[0089] Table 2 Effect of different heat relaxation treatments on the properties of the obtained FDY fibers

[0090] parameter Elongation at break % Breaking strength cN / dtex Single yarn fineness dtex Example 1 55 6.9 0.9 Embodiment 14 59 7.5 0.7 Embodiment 15 58 7.2 0.9 Example 16 57 7.3 0.8 Comparative Example 5 55 7.1 0.9

[0091] From Table 2, we can see that

[0092] Comparing Example 1 with Example 14, it can be seen that the FDY fiber parameters obtained in Example 14 are better, wherein the elongation at break and the breaking strength are improved, and the single filament fineness is reduced to increase the softness. It can be seen that the traditional relaxation heat treatment and the adjustment of water vapor and pressure in Example 14 can improve the elasticity and softness performance of the fiber;

[0093] By comparing Example 14 with Comparative Example 5, it can be seen that the relaxation heat treatment method of Example 14 has a better effect, that is, the adjustment of the pressure is necessary;

[0094] By comparing Examples 14 to 16, it can be seen that the parameters of Example 14 are more preferred.

Claims

1. A method for preparing soft ultra-elastic FDY fiber with improved air permeability, characterized in that: The following steps are involved: S1, slicing PET, polyamide and PTT respectively, then melting PET, polyamide and compounding agent in a mass ratio of 1:1:0.05-0.1, and extruding through a first spinneret, and then directly melting PTT and extruding through a second spinneret, the mass ratio of PET:PTT is 3:1-2; The composite agent is made of n-octyl phthalate, silicone oil and carbon nanotubes; the first spinneret adopts a gourd-shaped spinneret hole, and the second spinneret adopts a hollow spinneret hole; The number of the gourd-shaped spinnerets is a, the number of the hollow spinnerets is b, a:b is 3-4:8-9; the diameters of the gourd-shaped spinnerets are d1 and d2 respectively, the diameter of the hollow spinneret is d3, and d1=1.6-1.7d2, d3=d2; S2. After extrusion through the first spinneret and the second spinneret, fiber filaments are obtained, and the fiber filaments are spun in parallel to form a fiber filament, and then cooled by ring blowing, the temperature of the ring blowing is 20-30°C, and the wind speed is 0.5-1.4m / s, and then the FDY process and relaxation heat treatment are carried out in sequence to obtain FDY fiber.

2. The method for preparing a soft ultra-elastic FDY fiber with improved air permeability according to claim 1, characterized in that: The aspect ratio of the gourd-shaped spinneret is 2 to 3, and the diameter in the aspect ratio is d1.

3. The method for preparing a soft ultra-elastic FDY fiber with improved air permeability according to claim 1, characterized in that: d2 is 0.15~0.3mm.

4. The method for preparing a soft ultra-elastic FDY fiber with improved air permeability according to claim 1, characterized in that: In the FDY process, the FDY pre-network pressure is 0.05-0.2 MPa, the speed parameters are: the first roller speed is 2200-2280 m / min, the second roller speed is 3000-3200 m / min, and the winding speed is 2900-3000 m / min.

5. The method for preparing a soft ultra-elastic FDY fiber with improved air permeability according to claim 1, characterized in that: In the FDY process, the temperature parameters are: the spinning temperature is 272-275°C, the temperature of the first roller is 82-89°C, and the temperature of the second roller is 140-145°C.

6. The method for preparing a soft ultra-elastic FDY fiber with improved air permeability according to claim 1, characterized in that: The method of the relaxation heat treatment is: First, the composite gas is filled into the relaxation heat treatment equipment, and infrared heating is used to raise the temperature to 90-95°C, and the treatment is allowed to stand for 5-8 minutes. Then, the temperature is raised to 100-105°C, and the treatment is allowed to stand for 3-4 minutes. Then, the temperature is raised to 110-115°C, and the treatment is allowed to stand for 3-4 minutes. Then, the treatment is completed. The composite gas is N2 and CO2 in a mass ratio of 1:

1.

7. A method for preparing a soft ultra-elastic FDY fiber with improved air permeability as claimed in claim 6, characterized in that: The first static treatment is: filling 30% volume fraction of water vapor into the relaxation heat treatment equipment, and adjusting the pressure to 0.16-0.18MPa; the second static treatment is: filling 10% volume fraction of water vapor into the relaxation heat treatment equipment, and adjusting the pressure to 0.20-0.22MPa; the third static treatment is: adjusting the pressure to 0.16-0.18MPa.

8. The method for preparing a soft ultra-elastic FDY fiber with improved air permeability according to claim 1, characterized in that: The preparation method of the composite agent is: S1-1, first pre-treating the carbon nanotubes, the pre-treating method being: mixing the carbon nanotubes with 70% by mass concentrated nitric acid at a ratio of 1g:1ml, and soaking at 60-70°C for 2-3h; then rinsing the carbon nanotubes with deionized water, and drying at 60°C for 4-5h; obtaining the pre-treated carbon nanotubes; S1-2. Prepare n-octyl phthalate, silicone oil and pretreated carbon nanotubes in a mass ratio of 3:1 to 2:1, and then use a microfluidizer to mix them for 10 to 20 minutes to obtain a composite agent. The frequency of the microfluidizer is 100 to 150 times / s, and the working pressure of the microfluidizer is 300 to 350 MPa.

9. The method for preparing a soft ultra-elastic FDY fiber with improved air permeability according to claim 8, characterized in that: In step S1-1, after soaking for 2 to 3 hours, the carbon nanotubes are subjected to a plasma treatment in a plasma atmosphere with a power of 400 to 500 W and a time of 3 to 10 seconds. After being rinsed with deionized water, the carbon nanotubes are subjected to a secondary plasma treatment in a plasma atmosphere with a power of 600 to 650 W and a time of 2 to 3 seconds, and the plasma is argon.

Citation Information

Patent Citations

  • Method for preparing self-crimping fibers by taking recycled polyester as raw material

    CN112708947A

  • Production process of spiral two-component fiber non-woven fabric

    CN113293511A

  • No title available

    GB1290760A

  • Spinneret for melt spinning

    JP2001262428A

  • Hollow yarn with non-circle cross section and method ofmanufacturing the same

    KR1020060125161A